2016
DOI: 10.2196/jmir.4382
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personality Factors and Preceding User Comments on the Processing of Research Findings on Deep Brain Stimulation: A Randomized Controlled Experiment in a Simulated Online Forum

Abstract: BackgroundLaypeople frequently discuss medical research findings on Web-based platforms, but little is known about whether they grasp the tentativeness that is inherent in these findings. Potential influential factors involved in understanding medical tentativeness have hardly been assessed to date.ObjectiveThe research presented here aimed to examine the effects of personality factors and of other users’ previous contributions in a Web-based forum on laypeople’s understanding of the tentativeness of medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Laypeople’s understanding of the tentativeness of research findings was influenced by their personality factors and also by other users’ comments contributed to the forum. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Laypeople’s understanding of the tentativeness of research findings was influenced by their personality factors and also by other users’ comments contributed to the forum. 15 …”
Section: Introductionmentioning
confidence: 99%
“…Then we measured the participants’ perceived tentativeness of the findings described in the article using the perceived tentativeness scale (Feinkohl et al, 2016a, 2016b; Flemming et al, 2015). This scale consisted of six statements that participants had to rate on a 7-point Likert-type scale.…”
Section: Methodsmentioning
confidence: 99%
“…The users adopted the group’s social norm represented by the written comments of other users and adjusted their immediate responses (see also Kimmerle & Cress, 2009). Feinkohl et al (2016b) found that people who read skeptical comments that mentioned the tentativeness of the medical findings addressed more aspects of tentativeness when writing their own comment than when they read comments that did not address the tentativeness issue. Taken together, these considerations led to the assumption that skeptical user comments , that is, comments that take a very doubting and critical position toward the research finding reported in the journalistic article, might have an impact on the perceived tentativeness of research findings reported in online news articles.…”
Section: The Influence Of Different Types Of User Commentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Tentativeness, however, does not just infuence trustworthiness and credibility judgments. In a study by Feinkohl et al [23], participants saw an online news article about the therapeutic application of deep brain stimulation. Depending on the experimental condition, the article was accompanied by different online forum comments or no comments at all.…”
Section: Introductionmentioning
confidence: 99%